PEMBANGUNAN KARAKTER KEARIFAN LEGENDA SARIP TAMBAK OSO BAGI GENERASI - Joko Susilo; Niko Fediyanto (LPPM Universitas PGRI Adi Buana Surabaya, 2018)
Storytelling is a way to transfer knowledge from generation to generation, but sometimes the process is interrupted due to some disturbing factors from outside the cultural society. This program is designed to generate the activity of storytelling with